Simulation Models in Education - Stančić, Hrvoje (Array, 2007)
This paper introduces the use of simulation models in an e-learning environment. Nowadays, simulation models are a part of computer-assisted learning and thus an important guide for lifelong education. E-learning systems, combined with the use of simulation models as tool for interactivity, are the best way to provide some kind of virtual reality in education. Important techniques for building a usable simulation model are also presented. A good model has to be accompanied by texts, demonstration material, worksheets, teachers' guides, student manuals, as well as tools for the teacher in order to be able to make changes in the computer simulation program, like a text-editor, a graphic editor as well as a resource editor. In addition, the paper describes why it is important to follow the building scheme and discusses the problem of credibility. Than, these models are explained as a method of learning dependent on and independent from the use of computers and a view of its valuable aspects is shown. After presenting various examples from the primary and secondary schools to the university and in lifelong learning, examples of their use in information sciences have been presented, as well as need to include the course of building simulation model in the curriculum.